2021
DOI: 10.1186/s13287-021-02134-x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of retinal pigment epithelium and photoreceptors generated concomitantly via small molecule-mediated differentiation rescues visual function in rodent models of retinal degeneration

Abstract: Background Age-related macular degeneration (AMD) is a result of degeneration/damage of the retinal pigment epithelium (RPE) while retinitis pigmentosa (RP), an inherited early-onset disease, results from premature loss of photoreceptors. A promising therapeutic approach for both is the replacement of lost/damaged cells with human induced pluripotent stem cell (hiPSC)-derived retinal cells. Methods The aim of this study was to investigate the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Induced pluripotent stem cell (iPSC) can differentiate to RPE and photoreceptor cells. Transplantation of these derived cells has been shown to rescue light perception and visual function in RCS rats and NOD.SCID-rd1 mice [83]. Another study also demonstrated that the long-term treatment of iPSC-derived RPE and photoreceptor cells effectively protected Pde6b knockout rats [93].…”
Section: Prevention and Intervention Strategies Of Rpmentioning
confidence: 95%
See 1 more Smart Citation
“…Induced pluripotent stem cell (iPSC) can differentiate to RPE and photoreceptor cells. Transplantation of these derived cells has been shown to rescue light perception and visual function in RCS rats and NOD.SCID-rd1 mice [83]. Another study also demonstrated that the long-term treatment of iPSC-derived RPE and photoreceptor cells effectively protected Pde6b knockout rats [93].…”
Section: Prevention and Intervention Strategies Of Rpmentioning
confidence: 95%
“…For people with impaired vision, a typoscope can be worn to improve their vision for reading. Meanwhile, RPE [83], retinal photoreceptor cell [84], retinal progenitor cell [85], and iris pigment epithelial cell (IPE) [86], have been selected as candidates for cell transplantation, with varying results. Some studies have successfully established the cultivation of photoreceptor cells.…”
Section: Prevention and Intervention Strategies Of Rpmentioning
confidence: 99%
“…None of the animals showed abnormal proliferation or teratoma formation; however, the graft was compromised in two animals due to inflammatory response. 15 Interestingly, co-transplantation of RPCs and RPE cells derived from iPSCs was superior to transplanting individual cell types, it resulted in better visual response and preservation of ONL in a rat model of retinal degeneration. 16 Further, in an animal model of RP, subretinally transplanted iPSC-derived CRX-expressing photoreceptor precursors engrafted at the inner nuclear layer (INL).…”
Section: Preclinical Studies With Stem Cells Escsmentioning
confidence: 99%
“…Some of them required surgical interventions to facilitate retinal attachment. Other adverse effects include inflammatory response due to the injections of the cells 15 or its factors. 42 These adverse effects might be due to the invasive nature of intravitreal transplantation, and thus further research on the optimal delivery route for each disease type is required.…”
Section: Challenges With Stem Cells Therapymentioning
confidence: 99%
“…Loss of RPE cells will consequently result in loss of photoreceptors and subsequently blindness ( Hollyfield and Witkovsky, 1974 ; Miller et al., 2017 ; Mitrousis et al., 2020 ). Replacement of dead or dysfunctional RPE with stem cell-derived RPE along with photoreceptors is a promising alternative to treat age related macular degeneration (AMD) and some forms of retinitis pigmentosa (RP) ( Surendran et al., 2021 ). We suggest that the highly proliferative early RPE progenitor population in the CP spheres will provide an enriched and safe source to replace lost RPE in retinal degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%